Sociological reading of educational curricula and their role in inculcating the values of citizenship. The Arabic language books in the primary stage as a model - ben taher, noureddin (Journal of Social Sciences and Humanities, 2020)
The curriculum is one of the main pillars of the learning process: (Teacher, learner, curriculum), which consists of all the experiences, knowledge, values, and attitudes that the school provides to its learners. It is a pattern that stimulates the goals, content, evaluation and teaching methods, and that values are one of the educational goals that the curricula seek to establish in the learners' minds, where the interrelatational relationship between the integrated trio is considered; Citizenship, the educational curriculum, language, and the solid foundation upon which the learning process has been based since it was found in its modern perceptions The social processes that represent the sociological framework for understanding this relation are the knowledge basis given to language as a bearer of society's culture and identity, the first role in building these three important concepts for each human society, and this imperialist study came to inform the contents of the Arabic curricula in the primary stage of the values of citizenship. This is by achieving the core goal of knowing the role of new educational curricula in instilling citizenship values, using quantitative and qualitative content analysis as an authentic approach Using statistical methods (iterations, mean, percentages), the study found a series of findings, most notably: The Arabic curriculum at the primary level was not designed on the cultural and social basis, since it did not give importance to the values of citizenship in its three dimensions. While we see that the values of customs and traditions have taken considerable place in the reading books, we also find that the Arabic language curriculum seeks to consolidate the values and customs of Algerian society.